Single-pulse all-optical switching in amorphous DyxCo1-x and TbxCo1-x - Venkatesan, Munuswamy; Coey, John (My University, 2022)
Repeated uniform switching of the magnetization of thin films of ferrimagnetic amorphous Gdx(FeCo)1−x in response to single fast laser pulses is well established. Here, we report unusual toggle switching in thin films of sperimagnetic amorphous DyxCo1−x and TbxCo1−x with x ≈ 0.25 irradiated with single 200 fs pulses of 800 nm laser light. The samples have strong local random anisotropy due to the non-S state rare earth. The compensation temperature of the films is ≤180 K, and their Curie temperature is ≈500 K. They are largely switched by the first pulse, and subsequent pulses lead to partial re-switching of a decreasing amount of the irradiated area, with a granular structure of submicrometer regions of switched and unswitched material. Individual switched regions about 700 nm in size are observed around the edge of the irradiated spots where the fluence is at the threshold for switching. Results are discussed in terms of a random anisotropy model where the ratio of local anisotropy to exchange is temperature dependent.
PUBLISHED
Keywords: Ultrafast and Terahertz Spintronics; Femtosecond lasers; Thin films; Atomic force microscopy; Magnetic materials; Optical computing; Hall effect; Laser amplifiers; Ultrafast lasers; Phase transitions; Magnetic anisotropy; Nanoscience & Materials; Magnetism and spin electronics; Nanotechnology; Physics